2020
DOI: 10.1177/1055665619897233
|View full text |Cite
|
Sign up to set email alerts
|

Internationally Adopted Children With Unilateral Cleft Lip and Palate—Consonant Proficiency and Perceived Velopharyngeal Competence at the Age of 5

Abstract: Objective: To compare consonant proficiency, consonant errors, and the perceived velopharyngeal (VP) competence in internationally adopted (IA) children with unilateral cleft lip and palate (UCLP) and nonadopted (NA) children with the same cleft–palate type at age 5. Design: Case–control study based on phonetic transcriptions of standardized speech recordings of 5-year-olds at a tertiary hospital. Participants: Twenty-five IA children were compared to 20 NA children. All consecutive patients at a cleft lip and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 27 publications
5
14
4
Order By: Relevance
“…Previous studies of internationally adopted children with CLP have shown a high risk of speech difficulties, with poor articulation proficiency and velopharyngeal impairment lasting several years post‐adoption 5‐7,9 . In the present study, we found similar results for speech ability in the internationally adopted children with unilateral CLP, with a low PCC score at the age of 7‐8 years.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Previous studies of internationally adopted children with CLP have shown a high risk of speech difficulties, with poor articulation proficiency and velopharyngeal impairment lasting several years post‐adoption 5‐7,9 . In the present study, we found similar results for speech ability in the internationally adopted children with unilateral CLP, with a low PCC score at the age of 7‐8 years.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies of internationally adopted children with CLP have shown a high risk of speech difficulties, with poor articulation proficiency and velopharyngeal impairment lasting several years post-adoption. [5][6][7]9 In the present study, we found similar results for speech ability in the internationally adopted children with unilateral CLP, with a low PCC score the of 7-8 years. More 80% of the children with unilateral CLP scored 2 SD below the normative mean, but only 7% of those without CLP.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…18,19 Asian patients were also more likely than other races/ethnicities, with the exception of patients with other/unknown race/ethnicity, to have a complication. Although international adoption has been associated with worse speech outcomes compared to nonadopted infants in other studies, 20,21 a higher incidence of poorer palatoplasty outcomes within the 30-day postoperative period in Asian patients has not been previously described. It is unclear why this outcome disparity exists, especially in the absence of a higher incidence of preoperative surgical risk factors defined in NSQIP.…”
Section: Discussionmentioning
confidence: 85%